2009
DOI: 10.1111/j.1749-6632.2009.04614.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Rituximab Efficiency in Chronic Lymphocytic Leukemia by CpG‐Mediated Upregulation of CD20 Expression Independently of PU.1

Abstract: Lipopolysaccharide (LPS), CpG-containing phosphothioate oligonucleotides (CpG) and various cytokines impact chronic lymphocytic leukemia (CLL) B cells. For example, they influence cell cycle entry, expression of co-receptors, and CD20. Rituximab (RTX), for which CD20 molecule is the target, proved to be less efficient in CLL than in lymphoma. This is accounted for by a lower CD20 level in the former than in the latter B lymphocytes. CD20 transcription is mediated by four transcription factors, of which only pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Firstly, as described in CLL [27], we confirmed that CpG impact the first wave of effector cells by up-regulating the membrane expression of CD20 target molecules of Daudi human B cells (Fig. 1B left), and by inducing them into apoptosis through TLR9 with no effect on the density (Fig.…”
Section: Cpg-odn Drive Mø But Not Pmn To the B Cellssupporting
confidence: 78%
“…Firstly, as described in CLL [27], we confirmed that CpG impact the first wave of effector cells by up-regulating the membrane expression of CD20 target molecules of Daudi human B cells (Fig. 1B left), and by inducing them into apoptosis through TLR9 with no effect on the density (Fig.…”
Section: Cpg-odn Drive Mø But Not Pmn To the B Cellssupporting
confidence: 78%
“…MM cells have been shown to express TLR9 and to respond to CpG ODN by increased proliferation and survival (Bohnhorst et al, 2006; Jego et al, 2006). In chronic lymphoid leukemia, a CD20+ neoplasm, CpG ODN was shown to increase the level of CD20 expression after 24–48 h (Mankaï et al, 2009). To assess whether CpG ODN could induce or increase CD20 expression in myeloma cells, eight TLR9+CD20− HMCLs, BCN, JIM3, MDN, NCI-H929, RPMI8226, SBN, U266 and XG6, and one TLR9+CD20+ HMCL, Karpas 620, were cultured for 2 days with 5 μg/ml CpG ODN 2006.…”
Section: Resultsmentioning
confidence: 99%
“…In malignant and normal B-cells, CpG ODN increase CD20 expression at both protein and mRNA levels but the mechanism(s) are not known (Jahrsdörfer et al, 2001; Mankaï et al, 2009). The effect of CpG ODN is more difficult to analyze in our study because cells differentiate and loose their CD20 phenotype during this process.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional up-regulation of CD20 dependent on ERK phosphorylation was reported by Wojciechowski et al (30) in lymphoma and primary CLL cells treated with bryostatin-1. An increase in CD20 transcription was also shown to be triggered by CpG independently of PU.1 transcription factor in CLL cells (31). Epigenetic therapy also was reported to restore CD20 mRNA expression, a phenomenon observed in CD20-negative cells (15).…”
Section: Discussionmentioning
confidence: 96%